The Use of Politeness Strategies in Academic Conversations as Represented in a Corpus Linguistics MOOC - Mohamed Arafa Hilal (Journal of Pragmatics Research, 2023)
Although politeness strategies are widely used in various types of conversations, e.g., formal emails, business, hotel conversations, movies, and others, few works have dealt with politeness strategies in academic conversations. This study attempts to shed light on the use of politeness strategies in academic conversations and to relate these strategies to the relationship between the interlocutors: whether they have the same specialization or not. The study mainly draws on Brown and Levinson's positive politeness strategies and applies them to conversations. The data was collected by downloading conversations from a MOOC entitled "Corpus Linguistics: methods, analysis, interpretation," created by a team of corpus linguists at Lancaster College. It applies both a quantitative and qualitative approach to analyze the strategies. The results show that exaggeration tops the list of strategies with 23 utterances (23.5%) when the interlocutors have the same specialization. This indicates that each scholar has distinctive insights that another scholar only appreciates with the same specialization. When interlocutors have different specializations, the hierarchy of politeness strategies differs, albeit to some extent. Expressions of approval ranked first, with 11 expressions (25.0%). This indicates that a scholar with little knowledge about a branch of knowledge almost agrees with the specialized speaker.